Transitioning From S1P Receptor Modulators to B Cell–Depleting Therapies in Multiple Sclerosis: Clinical, Radiographic, and Laboratory Data. Issue 4 (17th July 2022) - Rowles, William M.; Hsu, Wan-Yu; McPolin, Kira; Li, Alyssa; Merrill, Steven; Guo, Chu-Yueh; Green, Ari J.; Gelfand, Jeffrey Marc; Bove, Riley M.
Abstract : Background and Objectives: Patients with multiple sclerosis (MS) transition from oral sphingosine-1-receptor (S1P) modulators to anti-CD20 therapies for several circumstances. Optimal timing of this transition is uncertain, given competing concerns of rebound disease activity and ensuring immune reconstitution. The objective of this study was to evaluate the relationship between inflammatory activity and the transition period from fingolimod to anti-CD20 therapies in a real-world MS cohort. Methods: Medical records were reviewed for all patients at our center transitioning from fingolimod to rituximab or ocrelizumab between 2010 and October 2020. Time periods reviewed were the following: before fingolimod discontinuation, interval between fingolimod and anti-CD20 treatments, and after the first anti-CD20 infusion. The primary outcome was clinical relapses; MRI activity, time to absolute lymphocyte count (ALC) recovery, and infections were secondary. Clinical and demographic factors significant in univariable analyses were included in multivariable analyses. Results: Transition data were available for 108 patients (68.5% women, 68.5% relapsing-remitting MS, mean age 44.6 years). The median (interquartile range) interval between fingolimod and anti-CD20 therapy was 28 (1–115.2) days. Six of 51 patients (11.8%) with intervals >1 month and 0/57 patients with shorter intervals experienced a relapse (MRI confirmed) within 6 months of fingolimod discontinuation. In the year following anti-CD20 initiation, 4/108 patients (3.7%) experienced a relapse (median 214.5 days after infusion). An additional 7% of those undergoing contrast-enhanced MRIs developed Gd+ lesions. ALC normalized following treatment switch in 89/92; the interval between treatments was unrelated to ALC recovery or infection. Discussion: Delaying anti-CD20 start to monitor ALC after S1P modulator discontinuation may not be necessary and could increase rebound risk. ALC monitoring could instead occur after a rapid switch to anti-CD20 treatment.